Production and addition of encapsulated biomineralizing bacteria in construction concrete (Research, Society and Development, 2023)
The use of calcium carbonate for closing cracks in concrete by the action of biomineralizing bacteria has been investigated. However, these bacteria are fragile and susceptible to the reaction medium, and they must be protected by encapsulation, until the moment they must carry out the biomineralization process. This research covered the study and optimization of the production of sodium alginate capsules for subsequent encapsulation of biomineralizing bacteria. The research also investigated the effect of these capsules (added in different percentages) in concrete masses using a CP II – E Portland cement (ABNT NBR Standard), formulated from the Andreassen equation. The samples were characterized in their fresh and hardened state. The swelling tests indicated that the sodium alginate capsules provided good conditions to receive the bacteria, to keep them alive and to be mixed in the concrete, presenting enough mechanical strength. Among the investigated conditions, the composition formulated using the Andreassen coefficient equal to q=0.37 and with the addition of 1.5% of sodium alginate capsules was the one that presented the most promising results; and after 28 days of curing, the mechanical strength to compression was 45.4 MPa, with the value within ABNT NBR 11578, since it establishes a minimum of 32 MPa.